2017
DOI: 10.1016/j.jaci.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Increased immune reactivity to central nervous system–derived naturally presented peptides in patients with active multiple sclerosis

Abstract: Disclosure of potential conflict of interest: R. Weissert serves on the board for Roche, Genzyme, Merck Serono, Biogen, and Novartis and receives grant support from Novartis and Sanofi Aventis. The rest of the authors declare that they have no relevant conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Myelin basic protein (MBP) is thought to be the major autoantigen which is involved (71, 72). Many researchers have addressed this topic and found additional myelin proteins that can be the target of the autoimmune response (1).…”
Section: Specific Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Myelin basic protein (MBP) is thought to be the major autoantigen which is involved (71, 72). Many researchers have addressed this topic and found additional myelin proteins that can be the target of the autoimmune response (1).…”
Section: Specific Diseasesmentioning
confidence: 99%
“…Moreover, proteins expressed on neurons and axons have also been discussed to be targets of the immune response in patients with MS based on work in EAE (76). Recently, in patients with MS, we have shown that peptides can be eluted from MHC molecules from CNS tissue that are recognized by T cells secreting IFN-γ (Th1) (72, 77). Importantly, the increased immune reactivity against such peptides is observed in patients with active MS, i.e., in patients with MS who have an acute bout- or/and contrast-enhancing lesions in the CNS indicating active inflammation.…”
Section: Specific Diseasesmentioning
confidence: 99%
“…Two additional peptides were sequences of tetanus toxoid ( 14 ) and JC virus ( 15 ) ( Table 2 ). The eluted ligands had been shown to induce elevated Th1 T cell responses in patients with active MS ( 10 ). All measurements were performed according to the manufacturer´s instructions (Mabtech, Nacka Strand, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we assessed the influence of treatment of alemtuzumab on auto-antigen-specific Th1 T cells. Potentially, these are the disease drivers in patients with active MS ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, all evidence, as mentioned by both sides of the current debate, is equally consistent with an "outside-in" versus "inside-out" pathogenesis. 1 As a result, and given the large body of work done on understanding the immunobiology of MS and the immunotherapeutics that sprang from these insights, Garber and Barnett's argument in favor of shifting gears toward improved therapies targeting degeneration and repair has merit.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%